2022
DOI: 10.1007/s00203-022-03111-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota in sports

Abstract: The influence of microbiota on the human body is currently the subject of many studies. The composition of bacteria colonizing the gastrointestinal tract varies depending on genetic make-up, lifestyle, use of antibiotics or the presence of diseases. The diet is also important in the species diversity of the microbiota. This study is an analysis of the relationships between physical activity, diet, and the microbiota of the gastrointestinal tract in athletes. This review shows the differences in the microbial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…As suggested in previous studies, we found that the characteristics of cancer patients, including sex, are related to the bacterial flora of the intestinal mucosa [ 20 - 24 ]. Previous studies have reported that the abundance of Bacteroides is related to physical activity in athletes and gait speed in healthy elderly women [ 25 , 26 ]. Another study reported a negative correlation between Enterobacteriaceae and gait speed in Parkinson’s patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As suggested in previous studies, we found that the characteristics of cancer patients, including sex, are related to the bacterial flora of the intestinal mucosa [ 20 - 24 ]. Previous studies have reported that the abundance of Bacteroides is related to physical activity in athletes and gait speed in healthy elderly women [ 25 , 26 ]. Another study reported a negative correlation between Enterobacteriaceae and gait speed in Parkinson’s patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity increases the amounts of bacteria mainly in the Clostridiales order and Lactobacillus, Prevotella, Bacteroides, and Veillonella species, and their numbers may vary depending on the sport type that the individual is involved in. These bacteria are mostly abundant in athletes whose sports activity requires high VO 2 max (37). Physical activity has been shown to have an effect on the qualitative and quantitative differentiation of the microorganisms capable of producing butyrate such as Clostridiales or Firmicutes (38).…”
Section: Discussionmentioning
confidence: 99%
“…It binds to the Toll-like receptor-4 of immune-competent cells and an inflammatory process occurs. At the same time, physical activity decreased the amount of lipopolysaccharide and stimulated the immune system (Mańkowska et al, 2022).…”
Section: Influences Of Various Types Of Moving Activities On Gut Micr...mentioning
confidence: 91%